Yellow River Basin: Living with scarcity - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2010)
The Yellow River Basin (YRB) Focal Project set out to study water poverty, water availability and access, water productivity, and water and related institutions in the Yellow River basin to develop and rank a series of high-priority interventions aimed at increasing water and food security for the poor, while maintaining environmental sustainability. The YBFP identified complex relations between water and poverty in the YRB; identified streamflow declines in the basin despite predicted higher rainfall; calculated basin-water shortfalls as a result of both economic development and climate change; assessed various aspects of rainfed and irrigated crop water productivity; and identified key reforms for water-related institutions. Moreover, the YBFP empirically assessed the benefits of agricultural water rights trading applying an innovative modeling framework to the basin.